BSADP mid term implementetion report: volume iv, evaluation data (Bauchi: Bauchi State Agricultural Development Programme, 1984)
The first year of the Statewide Agronomic Survey in Bauchi State was 1982. Eastern zone conduted the survey in 1981 during the establishment of the statewide programme and these results have been used to extrapolate the baseline for the state as a whole
osc 21/05/2019
Arch
Keywords: Agricultural economics; Agricultural production; Nigeria